2016
DOI: 10.1080/13880209.2016.1199041
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Schisandra chinensis extract on acne-related inflammation and UVB-induced photoageing

Abstract: Context: Schisandra chinensis (Turcz.) Baill. (Schisandraceae) fruit extract (SFE) has been reported to induce non-specific tissue protection against inflammation in vivo. However, the effects of SFE on Propionibacterium acnes-stimulated acne and UVB-irradiated photoageing have yet to be investigated. Objective: To systematically investigate the effects of SFE against P. acnes and photoageing in vitro. Materials and methods: Qualitative and quantitative analyses of SFE were performed by HPLC. SFE concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Pretreatment with the extract exerted positive effects on the antioxidant system, in particular the reduction in the glutathione levels induced by UVB irradiation was reversed by the presence of S. chinensis extract (the effect was statistically significant starting from 5 μg/mL). The MDA levels, compared to UVB-irradiated control group, were significantly decreased following the pretreatment with the extract (10 μg/mL) [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment with the extract exerted positive effects on the antioxidant system, in particular the reduction in the glutathione levels induced by UVB irradiation was reversed by the presence of S. chinensis extract (the effect was statistically significant starting from 5 μg/mL). The MDA levels, compared to UVB-irradiated control group, were significantly decreased following the pretreatment with the extract (10 μg/mL) [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Schisandrin B, at 10 mmol/L, inhibited NADPH oxidation in mouse liver microsomes incubated with carbon tetrachloride while at 110.0 μmol/L inhibited oxidation of erythrocyte membrane lipids induced by ferric chloride in vitro . On the other hand, the inhibitory effects of schisandra extract on acne‐related inflammation and UV‐B‐irradiated photo ageing revealed that it could dramatically alleviate the inflammatory responses in HDF cells, indicating its promising effects as a potent and efficient agent for acne therapy and photoaging prevention . Also, the highly oxygenated triterpenoid schinchinenlactone D, isolated from roots of schisandra, demonstrated prominent anti‐inflammatory properties .…”
Section: Major Medicinal Plants Used In Medication System As Anti‐agementioning
confidence: 99%
“…In our continuous investigations of novel bioactive agents from the endophytic fungi [ 23 , 24 ], the endophytic strain Aspergillus versicolor DY180635 isolated from the sea crab was selected based on the bio-evaluation results. The ethyl acetate extracts of a rice solid culture of A. versicolor DY180635 showed 80% inhibition on the anti-inflammation model of the Propionibacterium acnes -induced THP-1 cells at the concentration of 0.1 mg/mL [ 25 ]. High-performance liquid chromatography (HPLC) analysis of the ethyl acetate extracts indicated the presence of IDKPs with a diode array detector (DAD) through ultraviolet characteristics at λ max 236, 289, and 336 nm [ 26 ].…”
Section: Introductionmentioning
confidence: 99%